Successful management of severe anaemia in pregnancy: a rare case report - Ehigiegba, Oduware E.; Nwogoh, Benedict; Iweka, Reuben O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Severe anaemia in pregnancy is associated with high maternal and perinatal morbidity and mortality. The life-threatening complications associated with severe anaemia in pregnancy were averted in this case due to the astute management and multidisciplinary approach employed involving the hematologist, dietician, and obstetrician. We report a rare case of a 33-year-old pregnant woman with three living children who presented with severe anaemia, characterized by a hematocrit of 8% (haemoglobin of 2.5 g/dl) in her early second trimester of pregnancy. The peripheral blood smear revealed mixed nutritional deficiency anemia, while the bone marrow aspirate showed megaloblastic changes. She received blood transfusions, haematinics, vitamin supplements, and adequate nutrition. Following discharge, she attended weekly antenatal clinics with antenatal fetal surveillance until term. At term, she was induced and had vaginal delivery of a healthy baby. She was discharged healthy with her baby and had bilateral tubal ligation at 6 weeks postpartum for a completed family size. This case shows that the morbidities and mortalities associated with severe anaemia in pregnancy are preventable with good multidisciplinary clinical management. The severity of this anemia, her remarkable recovery, and successful outcome make this a rare and noteworthy case report.